2022
DOI: 10.3390/mi13020158
|View full text |Cite
|
Sign up to set email alerts
|

Design and Preparation of Self-Oscillating Actuators Using Piezoelectric Ceramics with High Coupling Factors and Mechanical Quality Factors

Abstract: Piezoelectric material properties were optimized to develop materials for an ultrasonic vibrator targeting a high vibration efficiency. Herein, novel materials were developed using a composition represented by 0.08Pb(Ni1/3Nb2/3)O3-0.07Pb(Mn1/3Nb2/3)O3-0.85Pb(Zr0.5Ti0.5)O3 + 0.3 wt.% CuO + 0.3 wt.% Fe2O3 with 0.3 wt.% Sb2O3 doping. A ceramic shape with a thickness of 2 mm was optimized using finite element analysis software, and high values of coupling factors (0.54) and mechanical quality factors (1151) were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In a previous study, Pb(Ni 1/3 Nb 2/3 )O 3 (PNN) and Pb(Mn 1/3 Nb 2/3 )O 3 (PMN), which are typical relaxor ferroelectric materials, were employed in Pb(Zr,Ti)O 3 (PZT) piezoelectric ceramics. It was confirmed that the PNN-PMN-PZT ceramic exhibited a high dielectric constant and piezoelectric properties [ 13 ]. The devices used in energy conversion application should possess excellent temperature stability even after long-term use.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, Pb(Ni 1/3 Nb 2/3 )O 3 (PNN) and Pb(Mn 1/3 Nb 2/3 )O 3 (PMN), which are typical relaxor ferroelectric materials, were employed in Pb(Zr,Ti)O 3 (PZT) piezoelectric ceramics. It was confirmed that the PNN-PMN-PZT ceramic exhibited a high dielectric constant and piezoelectric properties [ 13 ]. The devices used in energy conversion application should possess excellent temperature stability even after long-term use.…”
Section: Introductionmentioning
confidence: 99%